Ontogenesis of the fruit pulp layer of Hymenaea stigonocarpa (Fabaceae : Caesalpinioideae) - Paiva, EAS; Oliveira, DMT (CSIRO Publishing, 2004)
Hymenaea, a genus of major economic importance, has been the subject of several botanical studies. However, there is disagreement over the origin of the edible fruit pulp of Hymenaea, as there are no ontogenetic studies on this organ. According to some authors, the edible layer results from transformations of the mesocarp and endocarp, while according to others, it is considered a seed aril. There are still others who regard this layer as originating from an undefined region of the pericarp. To understand the nature and origin of the pulp layer, Hymenaea stigonocarpa Mart. ex Hayne ovaries and fruit were processed according to standard techniques. The production of the fruit pulp layer starts immediately after anthesis. During anthesis, the inner epidermal cells of the ovary show periclinal division and form a new layer of cells towards the mesocarp; this remains meristematic and initiates cell production by predominantly periclinal divisions, producing a compact tissue towards the locule. This tissue will become the fruit pulp layer, the inner endocarp. The seed coat shows typical testal structure without evidence of aril formation. This allows us to conclude that the fruit pulp layers are exclusively made from part of the endocarp. We also observed resin cavities on outer mesocarp and outer endocarp.